BUDAYA TRI HITA KARANA SEBAGAI PEMODERASI KOMPLEKSITAS TUGAS DAN TEKANAN WAKTU TERHADAP KINERJA AUDITOR - Musktikayani, Ni Luh Putu Desy; Dwirandra, A.A.N.B (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
This study aims to determine the effect of task complexity, time pressure on the performance auditors with tri hita karana culture as moderating the public accounting firm in Bali. The data collection method used was a questionnaire with non-probability sampling technique and obtained 42 samples. The data analysis technique used is multiple linear regression and Moderated Regression Analysis (MRA) to test the coefficient of determination, test the feasibility of the model and t test to test the hypothesis. Based on the results of this study indicate that the complexity of the task and the time pressures negatively affect the performance of auditors. This shows that the higher the complexity of the task and tenakan time in the process of auditing the auditor's performance will decrease. The results also showed the culture of Tri Hita Karana is not able to moderate the influence of the complexity of the task of the performance auditor, but the culture of the Tri Hita Karana able to moderate the effect of time pressure on the performance auditors.
Keywords: Task Complexity; Time Pressure; Culture Tri Hita Karana; Performance Auditor